2013
DOI: 10.1080/0022250x.2011.629063
|View full text |Cite
|
Sign up to set email alerts
|

How Do Cultural Classes Emerge from Assimilation and Distinction? An Extension of the Cucker-Smale Flocking Model

Abstract: When cultural tastes are not neutral but hierarchically matched to social status, people assimilate themselves to higher status by consuming cultural goods while distinguishing themselves from lower status by developing new tastes. Extending the Cucker-Smale model for mutual influence among agents, we examine when and how many cultural classes emerge from continuous distributions of tastes and what conditions those classes satisfy, through the assimilation-distinction mechanism. We simulate the models with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…The C-S model with weight ψ cs was introduced in 2007 by Cucker and Smale in [12] and was in some sense based on the paper by Viscek [36] from 1995 in which a model of flocking was introduced, such that each particle adjusted it's velocity with respect to the avarage velocity of it's neighbors. Since then existence, uniqueness, asymptotics and stability for alignment models similar to C-S (both in continuous and discrete cases) were extensively studied, both from physical and biological point of view [13] - [16], [30], [33] - [35] and from more theoretical point of view [1,2], [4] - [11], [17] - [25], [29,31]. A nice and thorough study of the C-S flocking model with a bounded communication weight can be found in [28], where the interplay between dicrete and continuous model is studied with measure valued solutions of the Vlasov type equation (1.3) or in [26], where the authors present a new, simple aproach to the problem of existence and asymptotics.…”
Section: Smooth Communication Weightmentioning
confidence: 99%
“…The C-S model with weight ψ cs was introduced in 2007 by Cucker and Smale in [12] and was in some sense based on the paper by Viscek [36] from 1995 in which a model of flocking was introduced, such that each particle adjusted it's velocity with respect to the avarage velocity of it's neighbors. Since then existence, uniqueness, asymptotics and stability for alignment models similar to C-S (both in continuous and discrete cases) were extensively studied, both from physical and biological point of view [13] - [16], [30], [33] - [35] and from more theoretical point of view [1,2], [4] - [11], [17] - [25], [29,31]. A nice and thorough study of the C-S flocking model with a bounded communication weight can be found in [28], where the interplay between dicrete and continuous model is studied with measure valued solutions of the Vlasov type equation (1.3) or in [26], where the authors present a new, simple aproach to the problem of existence and asymptotics.…”
Section: Smooth Communication Weightmentioning
confidence: 99%
“…In particular, an unexpected application was proposed by Perea, Gómez and Elosegui [27] who suggested to use the C-S flocking mechanism [11] in the formation of spacecrafts for the Darwin space mission. Recently, the C-S flocking mechanism was also applied to the modeling of emergent cultural classes in sociology and the stochastic volatility in financial markets [1], [15], [21].…”
Section: Introductionmentioning
confidence: 99%
“…4 This emergence of cultural diversity as an outcome of local consenses has been recently simulated using several agent-based models to capture more nuanced collective motions of multi-agent systems. 4,24,35 Among them, our interest lies in the first-order Cucker-Smale-type model 33 introduced for the emergence of cultural classes in human society due to assimilations and distinctions between agents. Other agent-based models for cultural diversity specify the rules of interactions between agents using verbal statements rather than mathematical equations and do not admit analytic proofs as opposed to simulation results.…”
Section: Introductionmentioning
confidence: 99%
“…33 to study the emergence of cultural classes, when both assimilation and distinction between agents are present in the dynamics, and the formation of clustering was numerically observed. Although the original Cucker-Smale model and its variants (see Refs.…”
Section: Introductionmentioning
confidence: 99%